(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This article examines one of the modern forms of fishing entities with various forms of ownership—the organization of fishing clusters—as well as the main criteria for their management mechanisms. Recommendations are provided on the role of clusters in the industry and their development paths.